Rancang Bangun Company Profile PT. Cassava Infra Media Berbasis Framework Codeigniter - Saifurrohman, Saifurrohman; Muhammad Zulfikar, Reza; Sutedi, Ade (Fuse-teknik Elektro, 2025)
The function of a company profile is as a company information media that can be accessed by anyone, both employees and the wider community. However, a company profile that still has shortcomings and obstacles requires a system that accommodates company profile information that can run dynamically. Therefore, the purpose of this study is to design and build a company profile website for PT. CASSAVA INFRA MEDIA. This Company Profile was developed using the Scrum Model methodology with the stages used being Product backlog, Sprint planning, Sprint backlog, Daily Scrum, Sprint Review, Sprint restropective. The framework used for this website is CodeIgniter with Unified Modeling Language (UML) modeling. The results of this study are a company profile website product as a media for information and promotional services so that it can improve the quality of the company.